Supervisi Akademik Kepala Sekolah Dalam Peningkatan Mutu Pendidikan - Syahbania, Eka Yoanita Rizqi (Proceedings Series of Educational Studies, 2024)
Abstract This research aimed to explore the role of academic supervision carried out by school principals in an effort to improve the quality of education at SMK Negeri 1 Kepanjen. The research employed a qualitative descriptive method with a case study at SMK Negeri 1 Kepanjen. Data was collected through observation, in-depth interviews with the principal, and teachers, and analysis of relevant documents. The research results showed that the school principal carried out academic supervision through three stages, namely planning, implementation, and evaluation. The planning stage included determining the objectives of coaching, scheduling, and the preparation of implementation plans by each teacher. The implementation of academic supervision consisted of regular supervision outside the classroom and clinical supervision within the classroom. Clinical supervision involved direct observation of classroom learning, followed by providing feedback and solutions to the identified weaknesses. Evaluation was carried out to determine the success of supervision and follow-up actions to improve teachers' skills. The findings indicated that academic supervision by the school principal played an important role in improving the quality of education. Effective supervisory practices included providing guidance, mentoring, and examples of teaching, as well as creating a collaborative culture within the school environment. However, challenges faced included the workload of the principal and resistance from some teachers. The research emphasized the importance of strong leadership, commitment, and interpersonal skills of the principal in facilitating quality academic supervision to achieve sustainable improvement in the quality of education. Abstrak Penelitian ini bertujuan untuk mengeksplorasi peran supervisi akademik yang dilakukan oleh kepala sekolah dalam upaya meningkatkan mutu pendidikan di SMK Negeri 1 Kepanjen. Penelitian menggunakan metode deskriptif kualitatif dengan studi kasus di SMK Negeri 1 Kepanjen. Pengumpulan data dilakukan melalui observasi, wawancara mendalam dengan kepala sekolah, guru, serta analisis dokumen terkait. Hasil penelitian menunjukkan bahwa kepala sekolah melaksanakan supervisi akademik melalui tiga tahap, yaitu perencanaan, pelaksanaan, dan evaluasi. Tahap perencanaan meliputi penentuan tujuan pembinaan, pembuatan jadwal, dan penyusunan rencana pelaksanaan oleh masing-masing guru. Pelaksanaan supervisi akademik terdiri dari supervisi reguler di luar kelas dan supervisi klinis di dalam kelas. Supervisi klinis melibatkan observasi langsung pembelajaran di kelas, diikuti dengan pemberian umpan balik dan solusi atas kelemahan yang ditemukan. Evaluasi dilakukan untuk mengetahui keberhasilan supervisi dan tindak lanjut untuk meningkatkan keterampilan guru. Temuan menunjukkan bahwa supervisi akademik oleh kepala sekolah berperan penting dalam peningkatan mutu pendidikan. Praktik supervisi yang efektif meliputi pemberian arahan, bimbingan, dan contoh pembelajaran, serta menciptakan budaya kolaboratif di lingkungan sekolah. Namun, tantangan yang dihadapi antara lain beban kerja kepala sekolah dan resistensi dari sebagian guru. Penelitian menekankan pentingnya kepemimpinan yang kuat, komitmen, dan keterampilan interpersonal kepala sekolah dalam memfasilitasi supervisi akademik berkualitas untuk mencapai peningkatan mutu pendidikan yang berkelanjutan.